A within‐coil optical prospective motion‐correction system for brain imaging at 7T. Issue 3 (20th February 2020) - DiGiacomo, Phillip; Maclaren, Julian; Aksoy, Murat; Tong, Elizabeth; Carlson, Mackenzie; Lanzman, Bryan; Hashmi, Syed; Watkins, Ronald; Rosenberg, Jarrett; Burns, Brian; Skloss, Timothy W.; Rettmann, Dan; et al.
Abstract : Purpose: Motion artifact limits the clinical translation of high‐field MR. We present an optical prospective motion correction system for 7 Tesla MRI using a custom‐built, within‐coil camera to track an optical marker mounted on a subject. Methods: The camera was constructed to fit between the transmit–receive coils with direct line of sight to a forehead‐mounted marker, improving upon prior mouthpiece work at 7 Tesla MRI. We validated the system by acquiring a 3D‐IR‐FSPGR on a phantom with deliberate motion applied. The same 3D‐IR‐FSPGR and a 2D gradient echo were then acquired on 7 volunteers, with/without deliberate motion and with/without motion correction. Three neuroradiologists blindly assessed image quality. In 1 subject, an ultrahigh‐resolution 2D gradient echo with 4 averages was acquired with motion correction. Four single‐average acquisitions were then acquired serially, with the subject allowed to move between acquisitions. A fifth single‐average 2D gradient echo was acquired following subject removal and reentry. Results: In both the phantom and human subjects, deliberate and involuntary motion were well corrected. Despite marked levels of motion, high‐quality images were produced without spurious artifacts. The quantitative ratings confirmed significant improvements in image quality in the absence and presence of deliberate motion across both acquisitions ( P < .001). The system enabled ultrahigh‐resolution visualization of the hippocampus during a long scan and robust alignment of serially acquired scans with interspersed movement. Conclusion: We demonstrate the use of a within‐coil camera to perform optical prospective motion correction and ultrahigh‐resolution imaging at 7 Tesla MRI. The setup does not require a mouthpiece, which could improve accessibility of motion correction during 7 Tesla MRI exams.